1983
DOI: 10.1007/bf00543800
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of aspirin and salicylate in elderly subjects and in patients with alcoholic liver disease

Abstract: Plasma aspirin, salicylate and salicyluric acid concentrations were monitored in young, elderly and alcoholic subjects after ingestion of a single 1.2 g dose of soluble aspirin. The plasma aspirin, salicylate and unbound salicylate concentration-time profiles varied considerably between individual subjects. Most of the pharmacokinetic parameters derived from these profiles were not significantly different between young subjects, elderly subjects and subjects with alcoholic liver disease. Individual plasma albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Due to their versatile use, ready availability over the counter and frequent use among the elderly, the pharmacokinetics of the salicylates in the elderly have been evaluated in a number of studies (Castleden et al, 1977;Salem & Stevenson, 1977;Cuny et al, 1979;Roberts et al, 1983). Castleden et al (1977), Cuny et al (1979) and Roberts et al (1983) have shown that most of the pharmacokinetic parameters were not significantly different between young and elderly patients, even though a marked increase in elimination half-life (Cuny et al, 1979) and apparent volume of distribution (Cuny etal., 1979;Roberts etal., 1983) was noted in the elderly group. However, no differences were noted in the area under the curve (AUC) of plasma salicylate concentration in these two age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their versatile use, ready availability over the counter and frequent use among the elderly, the pharmacokinetics of the salicylates in the elderly have been evaluated in a number of studies (Castleden et al, 1977;Salem & Stevenson, 1977;Cuny et al, 1979;Roberts et al, 1983). Castleden et al (1977), Cuny et al (1979) and Roberts et al (1983) have shown that most of the pharmacokinetic parameters were not significantly different between young and elderly patients, even though a marked increase in elimination half-life (Cuny et al, 1979) and apparent volume of distribution (Cuny etal., 1979;Roberts etal., 1983) was noted in the elderly group. However, no differences were noted in the area under the curve (AUC) of plasma salicylate concentration in these two age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the previous single dose studies of salicylate pharmacokinetics in healthy volunteers used a dose equivalent of greater than 1,200 mg of aspirin (Bochner et al, 1981;Day et al, 1988;Netter et al, 1984;Roberts et al, 1983). These studies required at least a 12 h period of frequent blood sampling and more than 24 h of urine collection.…”
Section: Discussionmentioning
confidence: 99%
“…study were similar to that found in other single dose aspirin studies (900 mg to 1,500 mg) with respect to AUC(SA), AUCu(SA), the apparent volume of distribution (V), peak SA plasma concentration (Cmax), time to peak (tmax) and SA clearance (CL(SA) etc. (Cham et al, 1980;Graham et al, 1977;Gunsberg et at., 1984;Roberts et al, 1983). Minor differences between the data sets can be attributed to variation in the mg kg71 dose, the age, sex and/or health status of the subjects involved in the various studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the dose administered, Sal has a half-life of between 2 and 15 h or more (Furst et al, 1979;Roberts et al, 1983). The present study used sodium salicylate (NaSal) because of its longer half-life and to eliminate the anticoagulant effect from the acetate moiety of aspirin.…”
Section: Introductionmentioning
confidence: 99%